Genomic analyses of Northern snakehead (Channa argus) populations in North America - Resh,Carlee A.; Galaska,Matthew P.; Mahon,Andrew R. (PeerJ, 2018)
Background The introduction of northern snakehead (Channa argus; Anabantiformes: Channidae) and their subsequent expansion is one of many problematic biological invasions in the United States. This harmful aquatic invasive species has become established in various parts of the eastern United States, including the Potomac River basin, and has recently become established in the Mississippi River basin in Arkansas. Effective management of C. argus and prevention of its further spread depends upon knowledge of current population structure in the United States. Methods Novel methods for invasive species using whole genomic scans provide unprecedented levels of data, which are able to investigate fine scale differences between and within populations of organisms. In this study, we utilize 2b-RAD genomic sequencing to recover 1,007 single-nucleotide polymorphism (SNP) loci from genomic DNA extracted from 165 C. argus individuals: 147 individuals sampled along the East Coast of the United States and 18 individuals sampled throughout Arkansas. Results Analysis of those SNP loci help to resolve existing population structure and recover five genetically distinct populations of C. argus in the United States. Additionally, information from the SNP loci enable us to begin to calculate the long-term effective population size ranges of this harmful aquatic invasive species. We estimate long-term Ne to be 1,840,000–18,400,000 for the Upper Hudson River basin, 4,537,500–45,375,000 for the Lower Hudson River basin, 3,422,500–34,225,000 for the Potomac River basin, 2,715,000–7,150,000 for Philadelphia, and 2,580,000–25,800,000 for Arkansas populations. Discussion and Conclusions This work provides evidence for the presence of more genetic populations than previously estimated and estimates population size, showing the invasive potential of C. argus in the United States. The valuable information gained from this study will allow effective management of the existing populations to avoid expansion and possibly enable future eradication efforts.
Keywords: 2b-RAD sequencing; Aquatic invasive species; Population structure; Effective population size; Genomic analyses; Single-nucleotide polymorphism